Are Dietary Restraint Scales Valid Measures of Dietary Restriction? Additional Objective Behavioral and Biological Data Suggest Not - Stice, Eric (2009)
Prospective studies find that individuals with elevated dietary restraint scores are at increased risk for bulimic symptom onset, yet experiments find that assignment to energy-deficit diet interventions reduce bulimic symptoms. One explanation for the conflicting findings is that the dietary restraint scales used in the former studies do not actually identify individuals who are restraining their caloric intake. Thus, we tested whether dietary restraint scales showed inverse relations to objectively measured caloric intake in three studies. Four dietary restraint scales did not correlate with doubly labeled water estimates of caloric intake over a 2-week period (M r = .01). One scale showed a significant inverse correlation with objectively measured caloric intake during a regular meal ordered from an ecologically valid menu (M r = −.30), but a significant positive relation that was qualified by a significant quadratic effect, to objectively measured caloric intake during multiple eating episodes in the lab (M r = .32). In balance, results suggest that dietary restraint scales are not valid measures of dietary restriction, replicating findings from prior studies that examined objective measures of caloric intake.